1972
DOI: 10.1084/jem.136.3.589
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Migration Inhibitory Factor (Mif)

Abstract: The initial interaction between migration inhibitory factor (MIF) and the guinea pig alveolar and peritoneal macrophage was studied. MIF-containing supernatants were generated from sensitized lymph node lymphocytes obtained from guinea pigs immunized with bovine gamma globulin in complete Freund's adjuvant. MIF-containing supernatants were markedly inhibitory for the migration of the peritoneal macrophage but had no effect on the alveolar macrophage. A linear relationship was observed between per cent inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
2

Year Published

1974
1974
1985
1985

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(16 citation statements)
references
References 20 publications
0
14
2
Order By: Relevance
“…Alveolar macrophages were capable of responding to MIF in this rabbit system, contrary to reported findings in guinea pigs (38). Although lymphocytes accounted for only 7% of respiratory cells, it has been shown (31) that as few as 1% sensitized lymphocytes are sufficient to inhibit the migration of a population of normal unsensitized macrophages.…”
Section: Methodscontrasting
confidence: 54%
“…Alveolar macrophages were capable of responding to MIF in this rabbit system, contrary to reported findings in guinea pigs (38). Although lymphocytes accounted for only 7% of respiratory cells, it has been shown (31) that as few as 1% sensitized lymphocytes are sufficient to inhibit the migration of a population of normal unsensitized macrophages.…”
Section: Methodscontrasting
confidence: 54%
“…The eluted fractions did not show any MIF activity, although in some cases the macrophage migration was reduced slightly (data not shown). DISCUSSION Leu et al reported that MIF could be removed from supernatants by incubation with macrophages (11). Other evidence of the presence of macrophage receptors for MIF was suggested by David et al, who showed that trypsinized macrophages failed to respond to MIF but regained their ability to do so after a 24 hr culture in vitro (7).…”
Section: Partial Purification Of Mif By Macrophage Cell Column Chromamentioning
confidence: 81%
“…Prior to development of the affinity column chromatography using macrophages, an investigation was performed to determine whether MIF can be adsorbed on live macrophages as reported by Leu et al (11). As shown in Table 1 (supernatants A & B), approx.…”
Section: Adsorption Of Mif On Peritoneal Macrophagesmentioning
confidence: 99%
See 2 more Smart Citations